Σχεδιασμός και υλοποίηση πρότυπου διαχειριστή ταυτόχρονων συνδιαλλαγών βασισμένο στον έλεγχο πολλαπλών εκδόσεων δεδομένων και υλοποίηση κατανεμημένου συλλέκτη μη έγκυρων δεδομένων για τη μη σχεσιακή βάση MongoDB - Γιαλούσης, Μιλτιάδης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Τεχνολογίας Πληροφορικής και Υπολογιστών, 2017)
Nowadays the rapid development of cloud computing alongside the rise in the number of the internet users, but also the services provided by it, has led to the evolution of the database management system (DBMS). A clear indication of this fact is the appearance of the NoSQL databases, like MongoDB, whose popularity was triggered by the needs of Web 2.0 companies such as Amazon, Google and Facebook and generally the advancements in the Big Data and real-time web applications. The purpose of this thesis is the design and implementation of a concurrent transactional manager based in the multiversion concurrency control (MVCC or MCC). The system which we implemented has been designed using the existing structure provided by CoherentPass, atop of who we created a level of abstraction providing us additional flexibility and the easy of manipulating the existing behavior. Furthermore, in the process of improving and extending the existing system we designed and realized a distributed garbage collector of invalid data versions for the MongoDB database, by developing a standalone Java application. This standalone Java application communicates with the various user applications through the expanded interface we provided and with the database through the MongoDB API provided by Java.